Zvýšení efektivity pracoviště pro výrobu obalů - Vorlická, Adéla (Vysoké učení technické v Brně. Fakulta podnikatelská, 2009)
Tato diplomová práce se zabývá návrhem na zvýšení efektivity ve výrobě obalů ve firmě SERVISBAL OBALY s.r.o. Cílem řešení jsou návrhy, které povedou ke zvýšení kapacity výroby na stroji „RODA Super-Combi 130 electronic“ a seznamuje s metodami zdokonalování výroby.

This diploma thesis deals with a proposal to increase the efficiency of package production in SERVISBAL OBALY s.r.o. company. The aim of the solution is to suggest methods for the production capacity improvement on the RODA Super-Combi 130 electronic unit and to inform about other production improving techniques.
Increasing of Effectiveness of the Package Manufacturing Workplace
Keywords: efektivita; organizování; plánování; proces; řízení; výroba; Efficiency; Organizing; Planning; Process; Direction; Production